Carbonic anhydrase VI exon 2 genetic polymorphism in Turkish subjects with low caries experience (preliminary study) - (:unkn) unknown (My University, 2011)
AIM: The aim of this study was to investigate carbonic anhydrase (CA) VI exon 2 genetic polymorphism and its possible association with low caries experience in healthy young adults. PATIENTS AND METHODS: Healthy young adults with caries or who where caries-free were recruited and unstimulated whole saliva and blood samples were taken. The number of decayed, missing and filled teeth (DMFT) and oral hygiene parameters were examined. Single nucleotide polymorphism (SNP) of CA VI gene exon 2 was determined by PCR and DNA sequencing. Salivary CA activity, buffering capacity and pH were also determined. RESULTS: Two SNPs (dbSNP: 142460367 and 142460368), which are responsible for amino acid changes, were found. The frequencies of these SNPs were not significantly different between the caries-free group and the group with caries. There was no correlation between these SNPs and the salivary parameters. CONCLUSION: Two SNPs found in young Turkish adults have no correlation with low caries prevalence.
Keywords: Female; Humans; Turkey; Male; Polymorphism, Genetic; Polymerase Chain Reaction; Base Sequence; DNA Primers; Exons; Carbonic Anhydrase IV